The Comparison Between Reading Aloud and Repeated Reading Strategy in Enhancing Student Reading Comprehension - Panjaitan, Nelson Balisar; Michael, Briyanna Ann (8ISC Abstract Proceedings, 2022)
The purpose of this study is to find out the improvement of students’ reading between those who were taught through Repeated Reading or Reading Aloud. This study used quantitative research methods and comparative design by using pre-test and post-test. This study was designed to find out the answer to the following question: Is there any significant difference in the students’ reading comprehension between those who were taught through Repeated Reading and those who were taught through Reading Aloud? The samples of this study are two classes in grade VIII of SMPN 1 Parongpong, Bandung. They were divided into two classes: grade VIII G experienced Repeated Reading, and grade VIII I experienced Reading Aloud. The instrument used for this study is a narrative text, which contains 33 questions. The result of this study shows that the students who acquired Repeated Reading or Reading Aloud method were improved for their reading comprehension, vocabulary enhancing as “moderate,” but there is no significant difference between those two groups of students ‘reading improvement. Keywords : RR (Repeated Reading) and RA (Reading Aloud)